Implementasi Metodologi Extreme Programming Pada Sistem Informasi Sekolah Dan Penerimaan Siswa Baru Berbasis Web - Saffana Assani'; Hermanto Hermanto; Muhammad Daviq Romadlon; Rizkiyatul Hurriyah; Muhammad Rizqi Hildani; Ahmad Ryan Al Baihaqy (Jurnal Ilmiah Informatika, 2023)
Madrasah Ibtidaiyah Miftahul Ulum III is a basic-level educational institution that requires a school information system and a new student admission system to be used in managing its school. In developing this system, a simple and fast system development methodology was chosen, namely extreme programming. The analysis used is functional and non-functional system analysis. For design, there are several types of design, namely database design using conceptual data models and physical data models, as well as system design using a unified modeling language. The research results at this stage are in the form of analysis documents and design documents that will be used for the implementation and testing stages